2017
DOI: 10.1167/iovs.16-20855
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Anatomical Outcomes in Patients With Serous Retinal Detachment in Diabetic Macular Edema Treated With Ranibizumab

Abstract: Similar BCVA gains were observed regardless of the presence of SRD. The higher visual gain usually observed in DME with SRD could be associated with a lower baseline BCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 23 publications
3
27
2
Order By: Relevance
“…Some studies found worse outcomes or no difference [15-17], whereas others support the finding in this study that better visual acuity gain is associated with the presence of subretinal fluid at baseline [18, 19]. …”
Section: Discussionsupporting
confidence: 70%
“…Some studies found worse outcomes or no difference [15-17], whereas others support the finding in this study that better visual acuity gain is associated with the presence of subretinal fluid at baseline [18, 19]. …”
Section: Discussionsupporting
confidence: 70%
“…Accordingly, it might be implicated in the regulation of this important physiological barrier and in the occurrence of macular edema, and in particular with the DME subtype associated with SRD. Although the pathogenetic theories at the basis of SRD occurrence are different, the role of RPE in retinal fluid homeostasis seems to be clinically confirmed by the results of the present series, since the DME patients showed a SRD incidence of 42%, which is in the high range compared to the 15%–45% reported in the literature [ 38 , 39 , 40 ]. However, we failed to demonstrate a significant differential expression of each of the downregulated miRNAs, including miR-199a-3p, between patients with and without SRD.…”
Section: Discussionsupporting
confidence: 83%
“…Determination of the morphologic and topographic characteristics of ME may help in elucidating the pathophysiology of the disease, which in turn helps predict the treatment response. [14][15][16][17] The morphologic features of ME on spectraldomain optical coherence tomography (SD-OCT) might be classified into three major types: diffuse retinal thickening (DRT), cystoid ME (CME), and serous retinal detachment. 18,19 Seo et al 20 reported that DRT showed a particularly good response to ranibizumab with fewer injections.…”
mentioning
confidence: 99%